The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/s0102-05362013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Okra seedlings production in protected environment, testing substrates and producing fruits in field

Abstract: The okra grows well in hot weather, finding favorable conditions for development in Brazil. We evaluated the production of okra seedlings and productivity. The experiment was conducted in the experimental area of the State University of Mato Grosso do Sul, in Aquidauana. In the seedling phase we tested substrates (100% triturated cassava stems, 75% triturated cassava stems and 25% vermiculite, 50% triturated cassava stems and 50% vermiculite, 25% triturated cassava stems and 75% vermiculite and 100% vermiculit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
1
0
2
Order By: Relevance
“…Existem muitos trabalhos relacionados à produção de mudas em diversas hortaliças, como abóbora (Higuti et al, 2010), alface (Domingues-Neto et al, 2016;Souza et al, 2008), beterraba (Oliveira et al, 2012), chicória Ustulim-Filho, 2013), couve-chinesa (Tessaro et al, 2013), melancia (Ramos et al, 2012), pimentão (Santos et al, 2010), quiabo (Costa et al, 2013), repolho (Cimó et al, 2017) e tomate (Rodrigues et al, 2010;Costa et al, 2012). No entanto, a maioria dos substratos estudados é produzida com materiais locais e de difícil reprodução por produtores de outras regiões.…”
Section: Introductionunclassified
“…Existem muitos trabalhos relacionados à produção de mudas em diversas hortaliças, como abóbora (Higuti et al, 2010), alface (Domingues-Neto et al, 2016;Souza et al, 2008), beterraba (Oliveira et al, 2012), chicória Ustulim-Filho, 2013), couve-chinesa (Tessaro et al, 2013), melancia (Ramos et al, 2012), pimentão (Santos et al, 2010), quiabo (Costa et al, 2013), repolho (Cimó et al, 2017) e tomate (Rodrigues et al, 2010;Costa et al, 2012). No entanto, a maioria dos substratos estudados é produzida com materiais locais e de difícil reprodução por produtores de outras regiões.…”
Section: Introductionunclassified
“…Evaluation of the yield capacity of vegetable seedlings after substrate or container tests was performed by Modolo et al (1999), Modolo et al (2001) and Costa et al (2013b) with okra, Leal et al (2011) with lettuce and beets, and Costa et al (2012a) and Costa et al (2013a) with eggplant, and the results indicating that high-quality seedlings increase yield. In studies with 128-cell expanded polystyrene trays, Seabra Júnior et al (2004) observed that the use of trays with larger volume (121.2 cm 3 ) resulted in earlier fruit harvesting than seedlings grown in trays with smaller volume (34.6 cm 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Um dos principais fatores que podem afetar a qualidade das mudas é o tipo de substrato, pois durante o período de germinação e desenvolvimento das mudas, o substrato deverá proporcionar condições hídricas e nutricionais satisfatórias. Com isto, vários estudos já mostraram que o uso de mudas com maior vigor resulta em plantas mais produtivas (Seabra Júnior et al, 2004;Leal et al, 2011;Costa et al, 2013bCosta et al, , 2015.…”
Section: Introductionunclassified